Sustainability of peacebuilding in aceh: an application of New Aceh scenario framework - Mursyidin, Nellis Mardhiah, Afrizal Tjoetra, Fiandy Mauliansyah,; Saputra, Jumadil (Opción, 2019)
The social change investment is continuously employed by Civil Society Organizations (CSOs) in Aceh. One of the efforts is to compile the documents of the Future Aceh Scenario (2007 - 2017). This study aims to determine the achievements of current changes compared to the time of the preparation of 2007 documents. The results obtained relate to the agenda of CSOs in Aceh to realize the New Aceh followed by the transformation of the roles and issues that CSOs have conducted in Aceh through policy advocacy, and actions related to the economic and social empowerment of communities